BETWEEN FORMAL AND INFORMAL THINKING: THE USE OF ALGEBRA FOR SOLVING GEOMETRY PROBLEMS FROM THE PERSPECTIVE OF VAN HIELE THEORY - Jupri, Al; Syaodih, Ernawulan (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
This study investigated primary education master program studentsâ problem solving strategies and their for-mal and informal thinking ability when dealing with geometry problems that require the use of algebra in its solution processes. In order to do so, an explorative study through individual written test, observation, and field notes, involving 47 primary education master program students was carried out. The perspective of Van Hiele theory on the development of geometric thought was used to interpret student formal and informal thinking strategy when dealing with geometry problems. The results showed that more than half of the stu-dents used informal rather than formal algebraic strategies in solving geometry problems; when students used algebraic strategies, their work were imperfect as they still made mistakes in applying the strategies. In the light of Van Hiele theory, it can be concluded that studentsâ level of thinking are still in between formal and informal thinking when dealing with geometry problems.